Pt@CeO2 Multicore@Shell Self-Assembled Nanospheres: Clean Synthesis, Structure Optimization, and Catalytic Applications - Wang, Xiao; Liu, Dapeng; Song, Shuyan; Zhang, Hongjie (Journal of the American Chemical Society, 2013)
A clean nonorganic synthetic method has been developed to fabricate the uniform pomegranate-like Pt@CeO2 multicore@shell nanospheres in a large scale. Under the effective protection of Ar atmosphere the redox reaction just simply happened between Ce(NO3)3 and K2PtCl4 in an alkaline aqueous solution, in which no other reducing agents or surfactants were added. The as-obtained nanospheres exhibited excellent structure stability even being calcined at 600 °C for 5 h. Moreover, the as-obtained Pt@CeO2 multicore@shell nanospheres can be further supported on reduced graphene oxide (RGO) to form heterogeneous nanocatalyst, which has been successfully applied in the chemical reduction reaction of nitrophenol (NP) by ammonia borane (NH3BH3, dubbed as AB) instead of hazardous H2 or NaBH4.